Thermal waters as cosmeceuticals: La Roche-Posay thermal spring water example - Seite S (Clinical, Cosmetic and Investigational Dermatology, 2013)
Sophie SeiteLa Roche-Posay Pharmaceutical Laboratories, Asnières, FranceAbstract: The curative use of thermal spring water is well known, but further investigation of its biological properties and therapeutic benefits is necessary. This present article reports all available scientific data concerning La Roche-Posay Thermal Spring Water and provides a better understanding of the biological mechanism of action of this water in regard to its composition and physicochemical properties and its clinical benefits for patients. These data justify the use of this selenium-rich water as an active or “cosmeceutical” ingredient in topical formulations to increase quality of life and compliance in patients with chronic disease.Keywords: thermal spring water, selenium, biological properties, curative use